PENGARUH LAMA PENYIMPANAN PADA SUHU KAMAR TERHADAP KUALITAS TELUR AYAM KAMPUNG YANG DIPELIHARA SECARA EKSTENSIF - I M. A. W., Atmaja; Dewi, G. A. M. K.; Indrawati, R. R. (Jurnal Peternakan Tropika, 2017)
The study aimed to determine how much the effect of the storage time at room temperature on the quality of chicken eggs with different length of storage time. This research was conducted at the Laboratory of Livestock Product Technology and Microbiology, Faculty of Animal Husbandry, Udayana University for a month. The study used a sample of chicken eggs which were maintained extensively as many as 60 eggs. The research design used was completely randomized design (CRD) with 4 treatments, namely: eggs that were stored for 0 day (P0), 7 days (P1), 14 days (P2) and 21 days (P3) at room temperature, each treatment was repeated three times with 5 eggs so that the total was 60 eggs, which aimed to strengthen the research data. Variables observed on egg quality test were; egg weight, eggshell weight, eggshell thickness, egg yolk color and Haugh units of eggs. The results showed there were no significant differences (P>0,05) on egg weight and egg yolk color that was influenced by the duration of storage, although the storage time of 14 days was better than without storage and stored for 7 days but the difference was not significant (P> 0,05), only the storage for 21 days (P3) which was markedly poorer color of egg yolk (P <0,05) compared with P2. While on the other treatments were not statistically significantly different (P> 0,05). Haugh units of eggs constantly decreased during storage. Storage for 14 days (P2) and 21 days (P3) was significantly (P <0,05) lower than P0 and P1, but P2 was not different (P>0,05) compared with P3. It can be concluded from the research result that the storage of chicken eggs reared extensively kept at room temperature for 0, 7, 14 and 21 days decreased the quality but it is still suitable for consumption up to 21 days storage time at room temperature.
Keywords: chicken, extensive, eggs, storage, egg quality